Pemanfaatan Pelepah Sawit dalam Pembelajaran Cermin di SMP Negeri 5 Satu Atap Tanjung Morawa - Rusti Lumban Gaol (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
Palm oil fronds can be utilized in the learning of flat, concave and convex mirrors. The development of palm frond mirror media is a solution because of the unavailability of tools that support learning and science laboratories. The research objective is to develop a palm oil frond mirror media so that it can be used in the learning process of flat, concave and convex mirror, and improve student learning outcomes by using the palm frond mirror media in discovery learning. The method used with the ADDIE model. The results of the study explained that the use of palm frond mirror media could improve student learning outcomes namely X ̅ = 33.72 to X ̅ = 82.08 g = 0.72 (high category), with students who had previously completed 6% to 89%. Palm frond mirror media is suitable for use in learning. This learning media is also effective in creating a pleasant atmosphere, students are active because they are directly involved in the process of making tools and concept discovery. The development of the media of palm frond mirror is able to build the character of students' scientific attitudes, namely discipline, honesty, care for the environment, and cooperation.